Physico-chemical properties of the top 120 m of two ice cores in Dronning Maud Land (East Antarctica) ... - Sarah, Wauthy; Jean-Louis, Tison; Mana, Inoue; Saïda, El Amri; Sainan, Sun; Philippe, Claeys; Frank, Pattyn (Zenodo, 2023)
We provide in this dataset the complete records from the top 120 m of two ice cores drilled on two adjacent ice rises (Hammarryggen and Lokeryggen, ~100 km apart) located in coastal Dronning Maud Land, Antarctica. Density, water stable isotopes (δ 18 O, δD and d-excess), ions concentrations (Na + , K + , Mg + , Ca + , MSA, Cl - , SO 4 2- and NO 3 - ), and continuous electrical conductivity measurement (ECM) records, as well as age models and resulting surface mass balance (SMB) are presented here. These ice cores are dated back to the end of the eighteenth century (CE 1793 ± 3 years for FK17and 1780 ± 5 years for TIR18) by manual and automatic multivariable layer counting and volcanic tie points validation. The SMB is calculated after correction for vertical strain rates. A detailed description of the measurement procedures, data treatments and uncertainties can be found in: Wauthy S., Tison, J.-L., Inoue, M., El Amri, S., Sun, S., Claeys, P., and Pattyn, F.: Physico-chemical properties of the top 120 m of ...